TEXTUAL AND LINGUISTIC CHARACTERISTICS OF RESEARCH ARTICLE ABSTRACTS - Amnuai, Wirada; Kotuta, Pansupa; Duangprasertchai, Maythinee (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
One of the most important parts of a research article is abstract. With limited space and words, writing English abstracts is a challenging task for inexperienced EFL writers. Analyzing the rhetorical structures and linguistic features of abstracts is a practical and effective way to assist unskilled writers in writing their abstracts correctly and provide them with a clearer insight into the genre. The present paper analyzes the rhetorical structures and linguistic features of English abstracts written by Thai authors. Data were collected from 30 applied linguistics abstracts published in six TCI-indexed journals. Verb tenses, voices, and interpersonal devices in the abstracts were examined. The findings showed that the product move was the most frequent. The occurrence of verb tenses and voice varied according to the moves. Both active and passive voice appeared frequently in the method move. The frequency of attitudinal markers was higher than that of other interactional resources. It was found in the present study that the employment of rhetorical moves with their linguistic characteristics and metadiscoursal devices can be a useful tool for Thai writers to write their research article abstracts in the field of applied linguistics. Besides, the findings will serve as a guideline for teachers in designing genre-related materials for teaching EFL learners.